Bioethanol production from Philippine Sargassum spp. - Borines, Myra Gumasing (2012)
This study focused on the pretreatment, enzyme saccharification and fermentation of locally available macroalagae, Sargassum spp., for bioethanol production. Proximate and structural analyses showed that the sample contained high amounts of carbohydrates and very low lignin. Using the two-level factorial design, ANOVA revealed that temperature, acid concentration and reaction time contributed significant effects on reducing sugar yield during the pretreatment of the macroalgal biomass. For the enzyme saccharification study, results showed that the effects of temperature, acid concentration and reaction time on glucose released were statistically significant (p < 0.05). Using the response surface methodology, the optimal acid pretreatment conditions were achieved at sulfuric acid concentration, temperature and reaction time of 3.4 to 4.6 % (w/v), 115 deg.C and 1.50 hr, respectively. The increase in cellulase loading from 5 FPU/g biomass to 50 FPU/g biomass had greatly increased the glucose conversion at the end of the 96 hrs of enzyme hydrolysis. Addition of B-glucosidase enzyme effectively prevented the accumulation of cellobiose in the hydrolysates. However, the addition of B-glucosidase had brought a significant increase in glucose yield only at lower cellulase loading. After fermentation by Saccharomyces cerevisae at 40 deg.C and a pH of 4.5 for 48 hrs, the % ethanol conversions obtained for different treatments were markedly higher that the theoretical yield based on glucose as substrate. Results showed that all the glucose present in the hydrolysate was consumed during fermentation, indicating the presence of other sugar sources other than glucose. The ethanol conversion was significantly influenced by the initial pH , temperature and incubation time. Kinetic study revealed that the maximum specific growth reaction rate, Umax is 0.141 hr-1 and the Monod constant, Ks is 0.301 g/Li. With these results, the macroalgae, Sargassum spp., showed significant potential as a renewable feedstock for the production of bioethanol.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Bioethanol; Sargassum -- Philippines